Abusive supervision and moral courage: does moral efficacy matter? - Ahmed Mohammed Sayed Mostafa (PSU Research Review, 2020)
Purpose – The purpose of this paper is to examine the role of both supervisory abuse and moral efficacy in the weakening or strengthening of moral courage. The study also tests how the interaction between both could influence moral courage. Design/methodology/approach – Cross-sectional data were collected from a sample of public hospital nurses in Egypt and structural equation modeling was used to analyse the data. Findings – The study findings revealed that abusive supervision is negatively related to moral courage whereas moral efficacy is positively related to courage. Furthermore, moral efficacy moderates the abusive supervision-moral courage relationship in such a way that the negative association between abusive supervision and moral courage is reduced when moral efficacy is high. Research limitations/implications – Because of the cross-sectional design of the study, inferences regarding causality cannot be made. Furthermore, more research is needed to identify whether the results of this study apply in other contexts. Practical implications – Organizations should identify abusive supervisors and offer them abuse-prevention training to circumvent their hostile behaviour. Organizations should also try to consider follower moral efficacy when matching supervisors with followers. Originality/value – The study addresses calls for research on the personal factors that could mitigate the undesirable effects of abusive supervision.